A NEW INTERPRETATION OF TRADITIONAL POETIC IMAGES IN THE POETRY OF HALIMA AKHMEDOVA (Conferencea, 2022)
Each word in the poetic text has a specific artistic meaning. In relation to other genres in literature, the poetic meaning of the word is fully realized in the poetic work. At the same time, it is possible to show a group of traditional poetic words related to the whole poetry. But this traditionality acquires an individual meaning in the work of a certain poet. At the same time, the active application of one or another artist to a specific poetic image becomes clear. There are no repetitions here. The originality of the artist can be seen in his ability to open new layers of meaning of the word. Every word in the language has an unlimited poetic potential. This possibility is brought to the surface only by the skill of the creator. If we compare the poetry of poets belonging to different eras, we will find active poetic words and figurative expressions specific to each era. There